2020
DOI: 10.1542/peds.2020-016915f
|View full text |Cite
|
Sign up to set email alerts
|

Helping Babies Survive: Lessons Learned From Global Trainers

Abstract: BACKGROUND: The Helping Babies Survive (HBS) suite of programs was launched in 2010 as an evidence-based educational package to train health care workers in low- and middle-income countries in neonatal resuscitation, immediate newborn care, and complications of prematurity. To date, there has been no purposeful examination of lessons learned from HBS trainers. Our intent with this study is to gather that data from the field. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Having local buy-in and integrating participants and stakeholders into the design of a programme is critical. In a recent comprehensive examination of lessons learned from trainers of the HBS programmes, having support and integrating education into the local context were identified as two major themes from facilitators [28]. Ensuring proper engagement with the target audience has also been highlighted as essential for global health educators [29][30].…”
Section: Selected Quotesmentioning
confidence: 99%
“…Having local buy-in and integrating participants and stakeholders into the design of a programme is critical. In a recent comprehensive examination of lessons learned from trainers of the HBS programmes, having support and integrating education into the local context were identified as two major themes from facilitators [28]. Ensuring proper engagement with the target audience has also been highlighted as essential for global health educators [29][30].…”
Section: Selected Quotesmentioning
confidence: 99%
“…Each pair uses a NeoNatalie (Laerdal Global Health) simulator, a low-cost mannequin that can demonstrate chest wall excursion and an umbilical pulse [ 4 ]. Since 2010, HBB has reached an estimated 850,000 providers in 158 countries [ 5 ]. In large-scale studies, HBB has been shown to decrease early neonatal mortality and fresh stillbirths in low- and middle-income countries (LMICs) [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Frequent practice both with self and peer-to-peer learning [ 11 , 14 , 15 ], as well as expert feedback have been shown to be helpful methods to sustain competencies [ 16 ]. In a recent qualitative study examining 10 years of HBB facilitator data, one of the themes that emerged as critical to the program was “frequent and sustained hands-on practice during and after the course [ 5 ].”…”
Section: Introductionmentioning
confidence: 99%